Pricing structure and strategies for Bako National Park / Japanie Bujang ... [et al.] - Bujang, Japanie; Kontot, Keria; Amin, Victor Luna (2007)
National Parks in Sarawak are common public property with SARAWAK FORESTRY as a management agent on behalf of the State Government of Sarawak. They are dully constituted under the National Parks and Nature Reserves Ordinance, 1998. National parks can have a wide range of economic benefits and uses. They may provide products for direct consumption, such as fish and game, as well as raw materials for production, such as rattan, timber and fish. But here, we are concerned mostly with the non-exploitative benefits and uses of national parks. Like any other protected areas of the world, they have universal appeal for recreation, tourism, conservation and ecosystem services. For some, products and services provided by biological resources markets do not exist, and there are no substitute markets from which to derive their value.